THE USE OF COMIC PICTURE IN IMPROVING STUDENT’S ABILITY IN WRITING NARRATIVE TEXT (ELang | An English Language Education Journal, 2019)
The research paper is entitled” The Use of Comic Picture in Improving Students’ Ability in Writing Narrative Text “(A pre-experimental study done at The Second Grade Students of Junior High School in MTs Negeri 1 Bandung)”. There were two aims of the research, those were to find out whether or not the use of Comic Picture as media has better result to improve Students’ Ability in Writing Narrative Text and to find out the students’ responses toward the use of Comic Picture as media to improve Students’ Ability in Writing Narrative Text. The population of the research were the eighth-grade students of MTs Negeri 1 Bandung. The sample of the research is class VIII-E. In obtaining the data, the writer used pre-test, post-test, treatment and questionnaire. From the computation of the pre-test and post-test scores, the result showed that with df = N1 = 33, at p = 0.5, the critical value of t-table is 2.141. The result of t-test on the pre-test was 20.77 lower than t-table (20.77 < 2.141). It means that there is no significant difference in the students’ mean score before and after treatment. The result of t-test on the post-test was 24.58 higher than t-table (24.58 < 2.141). The t-observed value was 9.435, so t-observed was higher than that t-table (9.435 > 2.141). It means that” The Use of Comic Pictures in Improving Students’ Ability in Writing Narrative Text “is effective. The result showed that questionnaire most students agreed that using comic picture can improve their writing ability. It means that almost all of the students gave positive responses towards the use of Comic Pictures in Writing Narrative Text.Keywords: Comic Pictures, Narrative Text.